A note on the 2019 president's budget - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2019)
The short note on the 2019 President's Budget attempts to assess the proposed shift from obligation-based to cash-based budgeting and its implications on the 2019 proposed national budget. In the process, it aims to inform policy deliberations on Senate Bill 1761 (formerly Senate Bill 1450), otherwise known as the Budget Reform Bill, by discussing the concept of cash-based budgeting with focus on its advantages and disadvantages and also, its implications on the 2019 proposed national budget and on government operations and practices. It also examines the past disbursement performance of the national government as well as the factors affecting their performance. The note argues for the need to reconsider DBM's initiative to shift from obligation-based to annual cash-based budget scheme in view of the perennial issues that government agencies/units have been facing.
Keywords: 330; government budget; obligation-based budget/appropriations; commitment-based budget/appropriations; cash-based budget/appropriations; annual cash-based appropriations; fiscal discipline; public financial management; Early Procurement Law; Budget Reform Bill; Budget Modernization Bill